Sectoral and geographical mobility of workers after large establishment cutbacks or closures - Eriksson, Rikard H; Hane-Weijman, Emelie; Henning, Martin (Environment and planning. A, 2018)
This paper studies redundant workers’ industrial and geographical mobility, and the consequences of post-redundancy mobility for regional policy strategies. This is accomplished by means of a database covering all workers who became redundant in major shutdowns or cutbacks in Sweden between 1990 and 2005. Frequencies of industrial and geographical mobility are described over time, and the influence of some important characteristics that make workers more likely to be subject to particular forms of mobilities are assessed. We find that re-employment rates vary extensively across industries and time. Whereas going back to the same or related industries is the most common re-employment strategy among workers who find a new job in the first year, workers who do not benefit from quick re-employment are increasingly squeezed out to new job fields and regions. Older workers and workers with high vested interest in their original industries usually employ a ‘same-industry/same-region’ strategy. This most frequent, and perhaps often most attractive, same-industry strategy comes at a cost, however. Individuals who instead pursue other mobility strategies have a lower risk of suffering from another major redundancy in the future. Thus, in terms of regional policy, strategies promoting diversification to related industries after major redundancies seem to be much more important than trying to retain workers in their old industry. In this case the route via education (university or vocational training) is important, as it increases the likelihood of successfully changing industry at time of re-employment.